(untitled) (Bangladesh Journal of Otorhinolaryngology, 2010)
Objective: To study the clinical, audiological and radiological characteristics along with the management outcome of chronic otitis media with effusion. Setting: Department of Otolaryngology & Head - Neck Surgery, Dhaka Shishu Hospital and Apollo Hospital’s Dhaka, Bangladesh. Materials and Methods: This study included three hundred and thirty patients of chronic Otitis media with effusion that have been treated in the department of Otolaryngology and Head-Neck Surgery, at Dhaka Shishu Hospital and Apollo Hospitals, Dhaka from January, 2007 to July, 2008. The data of patients included age, sex, presenting symptoms and signs, preoperative investigations like pure tone audiometry (PTA) and Impedance test, operation notes, complications of surgery and state at follow up. Results: This study included 198 males and 132 females. 222 patients (67.27%) were in the age group of 2-5 years. Main presenting symptom was fullness of the ear (50.30%) and main presenting sign was dull eardrum (72.18%). Turning fork test and PTA have been done in the age group of 7-10 years. In 166(59.30%) patients Impedence was type B. 222 (66.69%) patients have been cured with medical treatment. 69(20.90%) patients underwent grommet insertion as medical treatment has been failed in those patients. Two patients developed postoperative chronic suppurative otitis media with central perforation and one patient developed thinned tympanic membranes that have been treated conservatively. Conclusion: Chronic otitis media with effusion is usually not a threat to life but result in complications. As long as fluid is present in the middle ear, hearing will be affected. Hearing problems can interfere with language development in children. Any fluid that lasts longer than 3 months should be treated surgically. Keywords: Otitis Media with effusion; myringotomy; audiometry. DOI: 10.3329/bjo.v15i2.5057 Bangladesh J Otorhinolaryngol 2009; 15(2): 50-54